Analysing the choice and pattern of needs of transportation mode for domestic tourists in Bali. Issue 1 (February 2021) - Wiradnyana, I G N P; Suthanaya, P A; Wedagama, D M P; Yana, A A G A; Dissanayake, D
Abstract: Travel behaviour of domestic tourists concerning their choices of transportation mode has a significant role in managing traffic in the tourist destination. This study analyses the domestic tourists' choice and their pattern of needs of transportation mode in Bali as the case study. The developed models are based on utility maximisation of underlying preferences for each of the available modes of transport. Domestic tourists are randomly selected and interviewed using the questionnaire to record their daily trips. The study result indicates that income, number of visits and travel companions significantly influence the choice of transportation mode for domestic tourists. Meanwhile, income, number of visits, length of stays, trip purpose and main issues in selecting local transport mode significantly affect the pattern of needs of transportation mode for domestic tourists. For example, two accompanying persons will be three times more than that of seven persons or more to choose motorcycle and bus than a car. Domestic tourists who have visited Bali twice will be three times more than those who visited Bali once to use travel agents and rented vehicles than public and online transport and others. Further studies on short duration trips and sustainable mode of transport are suggested.